Efficacy, Durability, and Safety of Complete Endoscopic Mucosal Resection of Barrett Esophagus: A Systematic Review and Meta-Analysis. Issue 3 (March 2018) - Tomizawa, Yutaka; Konda, Vani J.A.; Coronel, Emmanuel; Chapman, Christopher G.; Siddiqui, Uzma D.
Abstract : Goals: To report the rate of eradication and recurrence of both neoplasia and intestinal mucosa and the rate of adverse events for complete endoscopic resection (CER) of Barrett esophagus (BE). Background: There is limited composite data on the clinical efficacy of CER of BE with high-grade dysplasia or neoplasia. Study: We performed a systematic review and meta-analysis of cohort studies that reported the clinical outcome of patients with BE who underwent CER and had at least 15-month follow-up after the time of elimination of BE. Main outcome of interests were pooled estimated rates of complete eradication of intestinal metaplasia and neoplasia, recurrence of intestinal metaplasia and neoplasia, and incidence of esophageal stricture, bleeding, and perforation. Results: We identified 8 studies reporting on 676 patients (high-grade dysplasia 54%) that met our criteria. Pooled estimated rates of complete eradication of intestinal metaplasia and complete eradication of intestinal neoplasia were 85.0% [95% confidence interval (CI), 79.4%-89.2%] and 96.6% (95% CI, 94.0%-98.1%), respectively, and rates of recurrence of intestinal metaplasia and recurrence of intestinal neoplasia were 15.7% (95% CI, 8.0%-28.4%) and 5.8% (95% CI, 3.9%-8.6%), respectively. Estimated incidences of adverse events were stricture 37.4 (95% CI, 24.4%-52.6%), bleeding 7.9% (95% CI, 4.4%-13.8%) and perforation 2.3% (95% CI, 1.3%-4.1%). Conclusions: CER achieves an 85% complete eradication rate of BE with recurrent rate of neoplasia of 6%. Estimated rate of postprocedural stricture was 37.4%. On the basis of this high rate of adverse events and significant heterogeneity in the studies included, the present meta-analysis cannot endorse CER as sole therapy for BE.